The Discourse Analysis of Diction Effects on Teachers Used in Teaching English as a Foreign Language - Muhammad Aswad; Ahmed Sardi (STAI Hubbulwathan Duri, 2023)
Proper diction relates to the choice of words used in conveying an idea. Diction in speaking becomes a difficulty for English teachers in classroom interactions. Especially for beginner English teachers, some of them are still unfamiliar with choosing the right/good vocabulary for describing and explaining material in teaching or using English to give some instructions. This study aimed at finding out the effect of diction used by the teachers during the interaction in the EFL class. This research applied qualitative research design and applied discourse analysis method specifically conversational analysis on the teachers’ utterances. Respondents who participated in this research were two English teachers and students respectively. The researchers collected the data through observation by recording teachers’ voices and interviews. This research found that the words or terms used by both teachers had an impact on the interaction, feedback and students’ interest in learning English. Miscommunication, misunderstandings, as well as a few feedbacks occurred in the classroom. There were a few learning aspects faced by both observed teachers to use proper word choice. They were a source of materials, teaching media and tools, as well as teacher training. All of them constrained those English teachers to employ the proper words during interaction in the classroom. Teachers are expected to be careful in choosing words or terms to establish communication between teachers and students.